2013
DOI: 10.1111/1755-0998.12184
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche models in phylogeographic studies: applications, advances and precautions

Abstract: The increased availability of spatial data and methodological developments in species distribution modelling has lead to concurrent advances in phylogeography, broadening the scope of questions studied, as well as providing unprecedented insights. Given the species-specific nature of the information provided by ecological niche models (ENMs), whether it is on the environmental tolerances of species or their estimated distribution, today or in the past, it is perhaps not surprising that ENMs have rapidly become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
189
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(191 citation statements)
references
References 192 publications
(286 reference statements)
2
189
0
Order By: Relevance
“…when studying genera or families that frequently diversified over millions of years. Phylogenetic comparative methods (Felsenstein 1985, Webb et al 2002 are typically (although not exclusively) used for a direct integration of niche models into phylogeographic studies (Chan et al 2011, AlvaradoSerrano andKnowles 2014). In an early avian study, Rice et al (2003) used SDMs to reconstruct the niche evolution in Aphelocoma jays and found strong deviation from niche conservatism; however, these results were contradicted by McCormack et al (2009).…”
Section: Multi-species Phylogeniesmentioning
confidence: 99%
“…when studying genera or families that frequently diversified over millions of years. Phylogenetic comparative methods (Felsenstein 1985, Webb et al 2002 are typically (although not exclusively) used for a direct integration of niche models into phylogeographic studies (Chan et al 2011, AlvaradoSerrano andKnowles 2014). In an early avian study, Rice et al (2003) used SDMs to reconstruct the niche evolution in Aphelocoma jays and found strong deviation from niche conservatism; however, these results were contradicted by McCormack et al (2009).…”
Section: Multi-species Phylogeniesmentioning
confidence: 99%
“…As a result of the rapid adoption of SDMs in the last decade, several aspects of SDM use and interpretation are actively evolving, including their application in phylogenetic studies and their ability to predict population density (Alvarado-Serrano and Knowles, 2014;Oliver et al, 2012;Pagel and Schurr, 2012). Many SDM studies compare alternative methodological approaches that help reduce or more accurately characterize uncertainty in the analysis of species-environment relationships (Dormann et al, 2008;Elith et al, 2006;Gritti et al, 2013;Synes and Osborne, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of genetic and environmental data in spatial frameworks has increased research perspectives in biogeography and evolutionary biology (Kozak et al, 2008;Alvarado-Serrano & Knowles, 2014). Such approaches have allowed characterizing species environmental preferences (Barata et al, 2012), identifying the potential location of past climatic refugia (Waltari et al, 2007), understanding the role of past climatic changes in spatial and genetic connectivity (Velo-Ant on et al, 2013), or studying the dynamics of hybrid zones (Tarroso et al, 2014).…”
Section: Introductionmentioning
confidence: 99%